Bio-Active Free Direct Optical Sensing of Aflatoxin B1 and Ochratoxin A Using a Manganese Oxide Nano-System - Singh, Avinash Kumar; Lakshmi, G. B. V. S.; Dhiman, Tarun Kumar; Kaushik, Ajeet; Solanki, Pratima R. (Frontiers in Nanotechnology, 2021)
Aflatoxins-B1(AFB1) and Ochratoxin-A (OchA) are the types of mycotoxin produced by Aspergillus flavus, Aspergillus parasiticus fungi, Aspergillus carbonarius, Aspergillus niger, and Penicillium verrocusumv. These toxins are mainly found in metabolite cereals, corn, coffee beans, and other oil-containing food items. Excess consumption of these toxins can be carcinogenic and lead to cancer. Herein, manganese oxide nanoparticles (MnO2 nps) have been proposed to explore the interaction with AFB1 and OchA using UV-visible spectroscopy. MnO2 nps were synthesized using the co-precipitation method. They were pure and crystalline with an average crystallite size of 5-6 nm. FTIR and Raman spectroscopy confirmed the MnO2 bond at their respective peaks. In the UV-vis study, the maximum absorbance for MnO2 nps was observed around 260 nm. The maximum absorbance for AFB1 and OchA was observed at 365 nm and 380 nm, respectively, and its intensity enhanced with the addition of MnO2 nps. Sequential changes were observed with varying the concentration of AFB1 and OchA with a fixed concentration of MnO2 nps, resulting in proper interaction. The binding constant (kb) and Gibbs free energy for MnO2 nps-AFB1 and OchA were observed as 1.62 × 104 L g-1 and 2.67 × 104 L g-1, and -24.002 and -25.256 kJ/mol, respectively. The limit of detection (LOD) for AFB1 and OchA was measured as 4.08 and 10.84 ng/ml, respectively. This direct approach of sensing AFB1 and OchA can be promoted as a potential analytical tool to estimate food quality rapidly and affordable manner at the point of use.